Overcoming Violence Against Children in School: Study on the Role of Education Stakeholders - Pramono, Wahyu (Universitas Negeri Semarang, 2018)
Data on violence against children are only a few reported but in reality more than reported. School is one of the locations of acts of violence against children. Preventing violence against children cannot just be handed over to the police, but must involve other education stakeholders in the school. This paper looks at the role of education stakeholders in preventing violence in schools. A qualitative approach used to understand the problems be researched, data taken by the use of in-depth interviews and obeservasi. The research was done in senior high shool Ã‚Â